Internet-enabled handheld devices, computing, and programming mobile commerce and personal data applications - Hu, Wen Chen, 1960-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book comprehensively reviews the state of handheld computing technology and application development"--Provided by publisher.
Section III. Client-Side Mobile Handheld Computing and Programming -- 10. Client-Side Handheld Computing and Programming -- 11. Java ME (Java Platform, Micro Edition) Programming -- 12. Advanced Java ME Programming -- 13. Palm OS Programming -- 14. Advanced Palm OS Programming -- Appendix -- Glossary -- About the Author -- Index.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on June 26, 2010).
Keywords: Mobile commerce; Electronic commerce -- Technological innovations; Business enterprises -- Computer networks; Mobile computing; Advanced WML; Client-side handheld computing; Client-side handheld programming; Electronic system structure; Handheld computing; Internet-enabled handheld devices; J2ME programming; Mobile commerce; Mobile handheld devices; Mobile networks; Mobile operating systems; Mobile security; Mobile-commerce networking; Palm OS programming; Personal data applications; Wireless markup language; Electronic books